Effect of different doses of sodium fluoride for female suckled albino rats on the reproductive efficiency of male infants and puberty - Hiba Jassim (College of Education for Pure Sciences, 2011)
Abstract This experiment was designed to study the effect treatment with sodium fluoride (200,400 ppm) with drinking water to mother rats during lactation on reproductive efficiency of their male pups at age of 21 days and to know the remaining of these effects on male rats at age of 50 and 90 days. Sodium fluoride (200 & 400 ppm) administration to mother rats with drinking water during lactation caused significant decrease in weights of body, testes, epididymal head, body, tail, prostate and seminal vesicle in their pups at 21 days old. Treatment with sodium floride to mother rats caused significant decrease in weights of the body, epididymal head, body, tail, seminal vesicle, number of sperm, with no significant changes in weights of testes and prostate in male rats at 50 days age. The study showed significant decrease in number of sperm, percentage of live sperm and significant increase in percentage of dead sperm and sperm abnormalities, with non significant changes in weights of body, testes, epididymal head, body, tail, prostate, seminal vesicle in adult male rat at 90 days age from mothers treated with sodium fluoride during lactation. Its concluded from this study that sodium fluoride has negative effects on reproductive efficiency of rat pups at 21 and 50 days age and this effect is less in male rats at 90 days age when their mothers treated with it during lactation.